2008
DOI: 10.1016/j.ijgo.2007.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Early oral hydration after cesarean delivery performed under regional anesthesia

Abstract: Objective: To establish an early, safe, and well-tolerated time to start oral hydration after cesarean delivery. Methods: A prospective randomized trial of women delivered by cesarean under regional anesthesia at Alanya Research and Medical Center, Turkey, between 2005 and 2006. A clear liquid drink was given to 100 women in the early oral intake (EOI) group 2 hours after surgery, and to 100 women in the delayed oral intake (DOI) group 8 hours after surgery. If the drink was tolerated, solid foods were then g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…However, Burrows (16) stated that early feeding has no effect on bowel sounds returning time and lzbiki (5) also reported no significant difference for hearing bowel sounds. Our findings are similar to that of some of previous studies (3, 6, 7, 9, 10, 17) but they are in disagreement with some others (5, 16). In the Izbiki and Burrows study (5, 16), experimental group started solid diet without hearing bowel sounds during the first 8 hours after surgery, while in the present study, the early feeding-group received clear fluid without hearing bowel sounds and they could start a regular diet after hearing bowel sounds.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, Burrows (16) stated that early feeding has no effect on bowel sounds returning time and lzbiki (5) also reported no significant difference for hearing bowel sounds. Our findings are similar to that of some of previous studies (3, 6, 7, 9, 10, 17) but they are in disagreement with some others (5, 16). In the Izbiki and Burrows study (5, 16), experimental group started solid diet without hearing bowel sounds during the first 8 hours after surgery, while in the present study, the early feeding-group received clear fluid without hearing bowel sounds and they could start a regular diet after hearing bowel sounds.…”
Section: Discussionsupporting
confidence: 71%
“…Statistical significant difference was found between the two groups for bowel sounds hearing time, first gas pass and first defecation time. Several studies also confirmed that post cesarean early oral intake caused faster bowel sounds return (10, 13, 16, 17). However, Burrows (16) stated that early feeding has no effect on bowel sounds returning time and lzbiki (5) also reported no significant difference for hearing bowel sounds.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…There were four studies that implemented oral intake within 2 hours after cesarean delivery. 22,24,25,28 However, the early intake was either a water or liquid diet. Most of the studies (n511) offered early oral intake within 6-8 hours after cesarean delivery, and the food provided among the eight studies included water, clear liquids, and solid food.…”
Section: Resultsmentioning
confidence: 99%
“…14 The most common nourishment provided to women for early oral intake was a liquid diet of tea, juice, water, or coffee (n511). 7,14,15,17,20,[22][23][24][26][27][28] A solid diet was provided in four studies. 8,16,19,21 A semiliquid diet or low-residue diet was introduced by only two studies.…”
Section: Resultsmentioning
confidence: 99%